FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP PENGHENTIAN PREMATUR PROSEDUR AUDIT (STIE Cendekia Karya Utama, 2020)
The purpose of this study was to determine the effect Variable Time Pressure, Audit Risk, Materiality, Review and Quality Control Procedures, Locus Of Controle, Professional Commitment Against Premature Termination Audit Procedures. The research sample is the auditor who worked on eight Public Accounting Firm ( KAP ) in Semarang , numbering as many as 62 auditors as respondents . Data were collected by questionnaire . Test the validity of using correlation Pearson Product Moment, while the reliability test using Cronbach Alpha. Classic assumption test including normality test, linearity test, test multicollinearity, and heteroscedasticity test . Test the hypothesis in this study using multiple regression analysis were processed with SPSS version 21. The results showed that the Time Pressure high and variable Audit Risk significant positive effect on Premature Sign Off. Variable Locus of Control, Professional commitment, Materiality,and Peer Review negatif effect on Premature Sign Off .